Arctic marine fish 'biotransformation toxicity' model for ecological risk assessment. (May 2019) - Fahd, Faisal; Veitch, Brian; Khan, Faisal
Abstract: Oil and gas exploration and marine transport in the Arctic region have put the focus on the ecological risk of the possibly exposed organisms. In the present study, the impacts of sea ice, extreme light regime, various polar region-specific physiological characteristics in polar cod ( Boreogadus saida ) and their effects on xenobiotic distribution and metabolism are studied. A Bayesian belief network is used to model individual fish toxicity. The enzyme activity in the fish liver and other pertinent organs is used as a proxy for cellular damage and repair and is subsequently linked to toxicity in polar cod. Seasonal baseline variation in enzyme production is also taken into consideration. The model estimates the probability of exposure concentration to cause cytotoxicity and circumvents the need to use the traditionally obtained No Observed Effect Concentration (NOEC). Instead, it uses biotransformation enzyme activity as a basis to estimate the probability of individual cell damages. Highlights: Bayesian Network Model with biomarkers as indicators of cell damage Model represents the combined impacts of sea ice and polar cods' physiology The model establish the dose response curves for PAH exposure on polar fishes.